O pensamento gráfico no cinema: a construção e a representação da imagem cinematográfica - Denser, Maria Teresa (2008)
This thesis inserts the graphic thinking in the theoretical reflections about cinema, analysing the aesthetic and mediatics phenomena that can be observed in movies, as a result of this thought. It is a theoretical descriptive proposition that tries to identify the parameters of the graphic aesthetics, in representation of the cinema s image as result of the filmmaker who uses simplified forms of the graphic expression to attend his objective of creation. For the questions of theoretical formulation, we utilized the theories of the cinema that board the aesthetics of the movie (Jacks Almont, Eric Rhomer), the cinema as language (François Albera, Sergei Eisenstein) and the theories formulated by the filmmakers (Sergei Eisenstein, Eric Rhomer, Píer Paolo Pasolini). The theory and practice of the cinema are approached through testimonies of the artists (Eisenstein, Fellini, Kurosawa, Hitchcock, Leone) and critic (Carlos Aguilar, Martin Scorsese). So that we were utilized the instruments of the genetic criticism (Cecília Almeida Sales) in the examination of the constructive processes in the production of the movies, Bronenosets Plotenkim (1925), Once Upon a Time in the West (1969), Kill Bill (2003) and Sin City (2005) what compose the corpus of analysys. The relevance of this research is due to the fact that this reflection has not considered space in the theories about cinema, meantime, the graphic thinking in the cinema is identified in this theory through the formal propositions put by the filmmakers who can be noticed in the result of this movies